Konteks Wacana dalam Buku Cerita Rakyat Riau Terbitan Dinas Pendidikan dan Kebudayaan Provinsi Riau - Vivi Yuniarti; Hermaliza Hermaliza (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
In a collection of Riau folklore, the author found that there is context in the form of setting, participants, results, mandate, methods, means, norms, and types in each story so that it makes the story interesting to read. The problem examined in this study is how is the context of the discourse in the Riau folklore book published by the Riau Province Education and Culture Office? This study aims to describe, analyze, and conclude the elements of the discourse context in Riau folklore books published by the Riau Province Education and Culture Office. The theory used in this study is the theory of Djajasudarma (2012), Darma (2014) and other supporting theories. The method in this study used descriptive methods, the approach used in this study was qualitative research and the type of research used was library research. Data collection techniques used are documentation techniques, hermeneutic techniques, and note-taking techniques. The results of this study found eight elements of the discourse context, namely elements (1) Setting and scene (2) Participants (3) Results (ends) (4) Message (5) Method (key) (6) Means (instrument) (7) Norms (norms) (8) Type (genre). Based on the analysis of the discourse context, it can be concluded that the data in the collection of Riau folklore books totals 222 data and all of these contextual data are the most important elements in building the story.